If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3x-3(1+1)=-15
We simplify the equation to the form, which is simple to understand
-3x-3(1+1)=-15
Reorder the terms in parentheses
-3x+(-6)=-15
Remove unnecessary parentheses
-3x-6=-15
We move all terms containing x to the left and all other terms to the right.
-3x=-15+6
We simplify left and right side of the equation.
-3x=-9
We divide both sides of the equation by -3 to get x.
x=3
| 55x=605 | | 2x+-2=10-4 | | 4y+9=17-2y | | 43+x=410 | | x-24=64 | | -3X^2+90=0 | | 5x=430 | | 4x-5y-9x+8y=0 | | 2x^2-lnx+1=0 | | 90-x^2=0 | | -x+3+12x=-4+4x+42 | | 5x-15x^3=5x(1-3x^2) | | (x+8)+4=x+(4+8) | | 3w^2-10w+8=0 | | -4(2+3n)=-56 | | 2(a+3)=5a-1 | | -4-4(2+4v)=-44 | | a-4(2a+4)=-44 | | 10a=45 | | 3(2+4x)=-42 | | 5(y^2-14y+49)=-90 | | 5x-12a=7-2x | | 2.4(m-3)+3.8=-32 | | 3x(x)+8x=9 | | 10n^2-9n=9 | | 6(y+x+2+x+4)=18 | | 3(x+1)+2(x+2)=2x+10 | | 5=(-6x-9) | | 6=-x^2+4x+2 | | 3(2-y)=2(1+3y)-7 | | -5k+1=1 | | -5x+3=2x^2-3x-1 |